2016
DOI: 10.1111/1744-7917.12363
|View full text |Cite
|
Sign up to set email alerts
|

Metatranscriptome of the protistan community in Reticulitermes flaviceps

Abstract: The hindgut of lower termites harbors various symbiotic protists, which perform varied functions in lignocellulose decomposition. As termites are social insects, the species and numbers of these flagellated protists in the termite gut vary among the different castes. Juvenile hormones (JHs) can regulate caste differentiation in termites. In this study, we used the juvenile hormone analog fenoxycarb to induce termite workers (Reticulitermes flaviceps) to differentiate into pre-soldiers. A metatranscriptomic inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…There has been no other study in the context of the higher termite gut microbiome that could serve as a guideline to the researchers to efficiently perform metatranscriptomic studies. This lack of methodology might be the primary reason for the scarce metatranscriptomic reports concerning the higher termite gut symbionts in comparison to their lower termite counterparts [ 18 , 50 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…There has been no other study in the context of the higher termite gut microbiome that could serve as a guideline to the researchers to efficiently perform metatranscriptomic studies. This lack of methodology might be the primary reason for the scarce metatranscriptomic reports concerning the higher termite gut symbionts in comparison to their lower termite counterparts [ 18 , 50 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, Warnecke et al [71] used a low-throughput metagenomic analysis to study the function of hindgut microbiota in the termite Nasutitermes ephratae (Holmgren), revealing a wide presence of genes responsible of cellulose and xylan hydrolysis. It has been also shown that protistan communities hosted by Coptotermes formosanus Shiraki and Reticulitermes flaviceps (Oshima) are responsible to positively influence lignocellulolytic system, thus enhancing insects’ nutrition [72,73]. The use of the microbiota associated with wood-feeding beetles as source of novel enzymes, potentially useful in industrial bioprocesses, has been investigated by different studies [74,75,76,77,78,79].…”
Section: Applied Perspectivesmentioning
confidence: 99%
“…The in-situ detection of flagellate protists, through metabarcoding approaches is available but requires database data for bioinformatics comparison to obtain organisms' identification and biological role inference. Other studies, such as meta-transcriptomics are actually overcoming the drawback of the need of protists individual identification and focus on protists community of symbionts functional role by transcript inference (e.g., on lignocellulolytic process; Scharf et al, 2011 ; Xie et al, 2012 ; Raychoudhury et al, 2013 , Liu et al, 2016 ). Even if the use of differential gene expression analyses for understanding community responses to specific conditions does overcome the need of flagellate protists species knowledge, these analyses do not contribute to our understanding of the protistan diversity nor to the identification of a given species (only community information) needed for a specific biotechnological purpose.…”
Section: Symbiotic Flagellate Protists: the Case Study Of Lower Termimentioning
confidence: 99%